DETERMINANTS OF FINANCIAL PERFORMANCE IN COAL MINING INDUSTRY COMPANIES LISTED ON THE BEI IN 2021-2022 - Danu Prayogo; Luke Suciyati Amna; Afrizal Nilwan (Transpublika Publisher, 2024)
The reason for this research is to test the effects of financial ratios such as Current Ratio, Debt to Equity Ratio, SIZE, and Return on Equity on the financial work of companies listed on the IDX in 2021-2022. Current Ratio, Debt to Equity Ratio, Return on Equity and SIZE as independent variables are used in this study, with ROA as the dependent variable. The population in this study is coal companies listed on the IDX in 2021-2022 using participants as many as 60 companies. The technique used in this study is known as purposive sampling (the process of determining the sample based on certain conditions). The type of information utilized in his research is secondary information obtained on the Indonesia Stock Exchange (IDX) for 2021-2022. The results of this study show that the Current Ratio has a positive insignificant impact on financial performance, the Debt to Equity Ratio variable has a negative insignificant impact on financial performance, the Return On Equity variable has a significant positive impact on financial performance and the SIZE variable has a positive insignificant impact on financial performance.